Implementation of Business Modeling Canvas (BMC) and Unified Modelling Language (UML) for Android-based Application - Fajar Akbar; Dedi Saputra; Irwan Agus Sobari Sobari; Erna Agustine (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
The development of digital in indonesia is shown from the increasing demand of computers use, and mobile Application. The development technology has an impact on changes in many human habits , especially in human's lifestyles.In this era People’s can get everything efficiently and effectively except in needs of foods. People can use VeggieFun for fulfillment fruits and vegetables needs. VeggieFun provides convenience people’s to order and buy fruits dan vegetables without go to market. As an application for comercial used, VeegieFun use bussines model and UML methode for development and implementation VeegieFun aplication. With a Bussines With Bussines Model Canvas (BMC) we can more get analiysis from bussines model and using UML In development of veggiefun applicationt for simplify the stages of implementation and development an application.Keyword : Busines Modeling Canvas, Unified Modelling Language, Application